Predefined-Time Super-Twisting Disturbance-Observer-Based Speed Control for PI-Based FOC Induction Motor Drives - Quang Huy Le; Ngoc Thuy Pham (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
This paper proposes a predefined-time super-twisting disturbance-observer-based speed control strategy integrated into a conventional proportional–integral (PI)-based Field-Oriented Control (FOC) framework for induction motor drives. Although PI regulators are widely adopted in industrial FOC systems due to their simplicity, low computational burden, and practical reliability, the mechanical speed loop remains vulnerable to load torque variations and parameter uncertainties, resulting in degraded transient performance and limited disturbance rejection capability. To address this issue, a predefined-time super-twisting disturbance observer is incorporated exclusively into the outer speed loop, while standard PI controllers are preserved for current and flux regulation, thereby maintaining structural simplicity and industrial compatibility. Specifically, a nonlinear predefined-time sliding manifold combined with time-varying adaptive gains is constructed to explicitly shape the convergence behavior and guarantee that the speed tracking error converges within a user-defined time independent of initial conditions and without requiring prior knowledge of disturbance bounds. Rigorous Lyapunov analysis establishes predefined-time stability of the disturbance estimation and overall closed-loop system. Simulation results under speed reversals, step load variations, and stochastic disturbances demonstrate that the proposed method achieves faster convergence, reduced overshoot, and enhanced robustness compared with conventional PI-based FOC, while preserving low implementation complexity and practical feasibility for industrial drive applications.